ROLE of FINANCIAL DEVELOPMENT for SOLVING the ENERGY INSECURITY in ASIA - Pichayakone Rakpho (2020)
© 2020 World Scientific Publishing Company. This study aims to investigate the nonlinear effect of financial development on energy security in Asia-16 countries over the period 2000-2016 using the proposed Panel Smooth Transition model for heterogeneity in time trends. Our model shows a single-threshold effect on financial development and energy security relationship, whereas energy accessibility, renewable energy share, and energy intensity are used as indicators of energy security. It implies that the sample can be split into two regimes: low- and high-FDI regime, we choose FDI as the threshold variable because it is a source of innovation that could reduce the demand for energy. The findings indicate that financial development goes hand-in-hand with energy accessibility and renewable energy share, and it also reduces the energy inefficiency in the economy. We also find that the contribution of financial development on renewable energy share becomes more substantial when the FDI is greater than the threshold point (0.9343% of GDP). However, the value of crude oil imports shows a negative impact on energy security in our empirical model.